The impact of maternal obesity on inflammatory processes and consequences for later offspring health outcomes. (27th March 2017) - Segovia, S. A.; Vickers, M. H.; Reynolds, C. M.
Abstract : Obesity is a global epidemic, affecting both developed and developing countries. The related metabolic consequences that arise from being overweight or obese are a paramount global health concern, and represent a significant burden on healthcare systems. Furthermore, being overweight or obese during pregnancy increases the risk of offspring developing obesity and other related metabolic complications in later life, which can therefore perpetuate a transgenerational cycle of obesity. Obesity is associated with a chronic state of low-grade metabolic inflammation. However, the role of maternal obesity-mediated alterations in inflammatory processes as a mechanism underpinning developmental programming in offspring is less understood. Further, the use of anti-inflammatory agents as an intervention strategy to ameliorate or reverse the impact of adverse developmental programming in the setting of maternal obesity has not been well studied. This review will discuss the impact of maternal obesity on key inflammatory pathways, impact on pregnancy and offspring outcomes, potential mechanisms and avenues for intervention.